Productivity of early table grape varieties in conditions of the seaside zone of Dagestan - A. G. Magomedova; M. K. Karaev (Овощи России, 2020)
Relevance and methods. The purpose of the research is an agrobiological assessment of introduced grape varieties of early ripening in the conditions of the Central seaside zone of Dagestan. The tasks of the study are to establish the timing of maturation of the studied varieties in the conditions of the Central seaside zone of Dagestan; to study agrobiological indicators of the studied varieties and to give an economic assessment; On the basis of the data obtained, to establish the degree of adaptability and prospects of the studied classes under these conditions. The objects of research were new introduced table grape varieties of early and early maturation period Augustine, Arcadia, Talisman, Attica, Kishmish luchisty. Results. The studies found that the introduced varieties of Arcadia, Attica, Talisman, Kishmish luchisty in the main agrobiological indicators surpass the Augustine variety widespread in this zone. According to the weight of the bunch, the varieties are distributed as follows: Kishmish luchisty – 724.5 g, Talisman – 676 g, Attica – 655.8 g, Arkadia – 514 g and Augustine (control) – 486 g. All varieties included in the experiment were more productive than control. The highest crop was provided by the variety Talisman – 28 t/ha. In second place is the Attica – 24.4 t/ha variety. Kishmish luchisty, despite the large mass of the bunch, provided a harvest of 22.6 t/ha. Arkadya variety in yield has close values to control – 18.2 t/ha. According to the adaptive index, the varieties were distributed as follows: Arcadia, Attica, Augustine and Talisman, with an adaptive coefficient of 0.71-0.85, are promising, and Kishmish luchisty with an adaptive coefficient of 0.69 is quite promising.